Penatalaksanaan Fisioterapi pada Kondisi Hernia Nukleus Pulposus Lumbal Untuk Meningkatkan Kemampuan Fungsional Lansia dengan Modalitas Tens dan Core Stability - Rani Fitria Dewi; Enny Fauziah; Arfian Hamzah (UPPM Politeknik Unggulan Kalimantan, 2024)
HNP is a degenerative process that causes decreased flexibility and thinning of the intervertebral disc nucleus pulposus resulting in tearing of the annulus fibrosus which causes low back pain which can interfere with functional activities in the elderly. The purpose of this study was to determine Management Physiotherapy of Hernia Nucleus Pulposus Lumbar Conditions For Increase Functional Ability Elderly With TENS Modalities And Core Stability. The type of research used is quantitative with a descriptive approach, namely a case study using 3 patient samples. Treatment was carried out 6 times within a period of 3 weeks. The measuring instrument used is the Oswestry Disability Index to determine the functional abilities of the elderly. The results of the study obtained after evaluation were an increase in the functional abilities of the elderly after providing interventions in the form of TENS and Core Stability. Keywords : Elderly, Hernia Nucleus Pulposus, Oswestry Disability Index, TENS, Core Stability